Influence of Soil pH and Farm Yard Manure Addition on Germination and Seedling Growth Attributes of Albizia Lebbeck Benth.( Kokko) - Masilamani, P.; Saravanapandian, P.; Annadurai, K.; Arulanandu, U. (Indian Forester, 2013)
An experiment was conducted to find out the influence of different soil pH and farm yard manure addition on seed germination, seedling growth and bio-chemical constituents of Albizia lebbeck. The seeds were sown in soil with different pH (8.1, 9.0, 10.2 and 10.5) and the soil with different pH mixed with sand + farmyard manure (2:1:1 ratio) compared with control (red earth + sand + farmyard manure at 2:1:1 ratio). Significant differences were observed among different treatments for all the parameters of germination and seedling growth attributes of 25 days old seedlings and survival percentage, seedling growth attributes and chemical constituents (Chlorophyll a, b and total and total N, P and K content) of 180 days old seedlings. This species is able to tolerate at extreme soil pH of 10.5, when the soil is mixed with sand and farm yard manure at 2:1:1 ratio, in terms of seed germination (49.0%), seedling growth and chemical attributes of the seedlings.